Effect of Calcination Temperature on the Crystallite Sizes and Stability of ZnO Nanoparticles Synthesized via Green Method Using Eucalyptus (Melaleuca leucadendra) Leaf Extract - Cahyani, Intan Sophia; Nurmalasari, Devi; Panatarani, Camellia (JIIF (Jurnal Ilmu dan Inovasi Fisika), 2025)
Synthesis of zinc oxide (ZnO) nanoparticles is a growing research field with wide applications in electronic equipment. pharmaceuticals. optics. and food packaging. This study aims to investigate the effect of calcination temperature on the cristallite size and stablity of ZnO nanoparticles synthesized by the sol-gel method with and without the addition of eucalyptus leaf extract (Melaleuca leucadendra). The calcination process was carried out at temperatures of 400°C, 600°C, and 800°C. Sample characteristics were observed using XRF, FTIR, XRD, PSA, ZETA, and PL. XRD characterization showed that all samples had a hexagonal wurtzite crystal structure, with increasing temperature resulting in higher crystallinity and larger crystallite sizes, reaching 78.71 nm at 800°C for the sample without extract and 32.81 nm for the sample with extract. PSA analysis showed that the particles with extract had a more uniform size distribution, especially at 800°C. The zeta potential values ranged from -43mV to -57mV, indicating good colloidal stability. UV-Vis spectra showed that the energy of the exclusion band (Eg) increased with temperature, with the highest value (3.52eV) in the sample without extract at 800°C. These results indicate that the calcination temperature plays a crucial role in improving the crystal quality and particle stability. Meanwhile, the addition of eucalyptus leaf extract acts as a natural stabilizing agent that helps reduce crystal defects. Keywords: ZnO nanoparticles, calcination temperature, eucalyptus leaf extract, crystal size, particle stability